Students’ Attitude Toward Pursuance of Higher Education in Abroad Study: A Study Among Grade 12 Students in Pokhara - Timilsina, Pusparaj; Bhurtel, Sima (Kalika Journal of Multidisciplinary Studies, 2024)
This article, ‘Students’ Attitude toward Pursuance of Higher Education in Abroad Study: A Study among Grade 12 Students in Pokhara’ is prepared by investigating the pertinent reasons for motivating students going abroad for higher education after completing grade twelve in Nepal. This research is guided by the objectives to study grade 12 students’ views about going abroad for higher education and to explore the migration trends in the resent years in the context of Nepal. Field visit, informal interview and the questionnaire are the major research tools for data collection. Both the qualitative and quantitative methods are used to process the received data and they are presented in the tables, charts, graphs, etc. The final data are analyzed both in numerical and theoretical interpretations. The results indicate that a large number of students are willing to go abroad for education or for job purposes whereas some students think about continuing their study here in Nepal after completing grade 12. Only one third students do not have a concrete plan for going abroad currently. Similarly, more than half of the students have a plan to go abroad in future once in their life for education which is a challenging question for our education system in Nepal and it is recommended to bring the applicable policy and create the ample opportunities for students to keep them back in the country.